2014
DOI: 10.1212/wnl.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset Alzheimer disease genetic variants in posterior cortical atrophy and posterior AD

Abstract: Objective: To investigate association of genetic risk factors for late-onset Alzheimer disease (LOAD) with risk of posterior cortical atrophy (PCA), a syndrome of visual impairment with predominant Alzheimer disease (AD) pathology in posterior cortical regions, and with risk of "posterior AD" neuropathology. Methods:We assessed 81 participants with PCA diagnosed clinically and 54 with neuropathologic diagnosis of posterior AD vs 2,523 controls for association with 11 significant single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 30 publications
9
36
0
2
Order By: Relevance
“…ABCA7 is involved in lipid metabolism and transport, and is a possible link between cardiovascular risk factors and AD (Stampfer, 2006; Jones et al, 2010; Reitz et al, 2013). Furthermore, ABCA7 has been shown to be nominally associated with the brain atrophy in the posterior portion of the cerebral cortex (Carrasquillo et al, 2014), which is consistent with the significant cluster identified in this study.…”
Section: Resultssupporting
confidence: 90%
“…ABCA7 is involved in lipid metabolism and transport, and is a possible link between cardiovascular risk factors and AD (Stampfer, 2006; Jones et al, 2010; Reitz et al, 2013). Furthermore, ABCA7 has been shown to be nominally associated with the brain atrophy in the posterior portion of the cerebral cortex (Carrasquillo et al, 2014), which is consistent with the significant cluster identified in this study.…”
Section: Resultssupporting
confidence: 90%
“…Clinically, they all relatively spare memory, and pathologically, they may all have hippocampal sparing with greater posterior cortical NFTs 44 . There is additionally specific involvement of left hemisphere language areas in lvPPA 80,91 and the visual neocortex in PCA 92,93 . Neuroimaging data also suggest posterior neocortical rather than mesotemporal cortical overlap of these phenotypes 78,94,9578,94,95 .…”
Section: Introductionmentioning
confidence: 99%
“…Amyloid PET scan is abnormal in PCA patients with AD but the distribution is hard to distinguish from AD[5] however tau PET scan shows disproportionate tau deposits in the visual areas[6]. Recently Carrasquillo and colleagues[7] found ApoE to be related to PCA and indicated that, CLU, BIN1 and ABCA7 may be related but further study is needed.…”
Section: Focal Cortical Presentations Of Alzheimer’s Disease(ad)mentioning
confidence: 99%